Thalassemia...Who is to be screened? - Niveen Salama; Omnia Y. Abd El Dayem; Doaa Shaltout; Mariam Saad Nassim (Pediatric Sciences Journal, 2024)
Background: Thalassemia carrier rate in Egypt is as high as 9-10%. The first step to eradicate thalassemia is to define population at risk. Aim of the work: to define the high risk population to be screened for thalassemia. Subjects and Methods: This observational cross-sectional study included children aged between 1 and 16 years presenting with microcytic anemia to Cairo university Children Hospitals from the period between March and September 2022. Children with hemoglobin <10mg/dL and mean red blood corpuscle volume (MCV) <70fl were included in the study. Complete blood count, serum ferritin, and hemoglobin electrophoresis were done. Results: Out of a total of 180 patients, 120 patients (66.7%) had iron deficiency anemia, 2 patients (1.1%) had alpha thalassemia, and 14 patients (7.7%) had beta thalassemia, 14 (7.7%) patients had thalassemia trait, 3 (1.67%) had sickle thalassemia, 7 (3.88%) had combined iron deficiency anemia (IDA) and thalassemia, and 20 (11.1%) required further investigations. Patients were divided according to MCV into 3 groups MCV<60, 60-65, >65. There was no significant difference in the diagnosis between the three groups. Conclusion: 22 % of children with MCV < 70 fl were found to have an inherited hemolytic anemia. Children with MCV <70 should be screened for thalassemia.